EUS-Assisted Evaluation of Rectal Varices before Banding - Malay Sharma; Praveer Rai; Raghav Bansal (Gastroenterology Research and Practice)
Rectal varices are an important cause of bleed. The bleeding can be sometimes fatal. Endoscopic management is possible and is generally done in emergency situation. Rectal variceal banding is useful. Hemodynamic evaluation has shown that the blood flow in rectal varices is from above downwards; however, the site of banding of rectal varices is unclear. This case series shows that the rectal varices should be banded at the highest point of inflow.